mRNA COVID-19 vaccine safety among children and adolescents: a Canadian National Vaccine Safety Network cohort studyResearch in context - Phyumar Soe; Otto G. Vanderkooi; Manish Sadarangani; Monika Naus; Matthew P. Muller; James D. Kellner; Karina A. Top; Hubert Wong; Jennifer E. Isenor; Kimberly Marty; Hennady P. Shulha; Gaston De Serres; et al. (The Lancet Regional Health. Americas)
Summary: Background: The Canadian National Vaccine Safety Network conducted active safety surveillance for COVID-19 vaccines. This study aimed to characterize the short-to-medium term safety of mRNA COVID-19 vaccines across the pediatric age spectrum. Methods: In this cohort study, vaccinated and unvaccinated children and adolescents aged 6 months to 19 years from eight Canadian provinces and territories were invited to participate. The outcome was a health event preventing daily activities, resulting in school absenteeism, or requiring medical consultation. Age-stratified multivariable regression models were used to examine health events associated with first and second doses of mRNA COVID-19 vaccines across different age groups: children under 5, children aged 5–11 years and adolescents aged 12–19 years. Findings: From January 2021 through February 2023, a total of 259,361 individuals from the dose one survey, 131,032 from the dose 2 survey, and 1179 from the control survey were included. In the week following dose two, vaccinated adolescents showed a higher proportion of health events [794 (4.6%) of 17,218 BNT162b2 recipients, 98 (8.5%) of 1153 mRNA-1273 recipients, 49 of (10.6%) of 464 heterologous schedule recipients] than unvaccinated adolescents [9 (3.7%) of 242 controls], but most events were self-limited and resolved within 7 days. No significant differences in proportion of health events following mRNA COVID-19 vaccines were observed between vaccinated and unvaccinated groups among adolescents after dose 1, or among children under 5 or those aged 5–11 years after any dose. Reported myocarditis/pericarditis cases within 0–28 days peaked among male adolescents following dose 2, in three of (0.037%) 8088 homologous BNT162b2 recipients, and two of (0.529%) 378 homologous mRNA-1273 recipients. Interpretation: Our findings suggest that reported health events, including myocarditis/pericarditis, vary by pediatric age group. Vaccinated adolescents reported health events more frequently following the second mRNA COVID-19 vaccine dose, while younger age groups did not report events more frequently than their unvaccinated counterparts. Funding: Canadian Immunization Research Network, Canadian Institutes of Health Research; Public Health Agency of Canada; COVID-19 Immunity Task Force.